2016
DOI: 10.1038/bmt.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Decreased morbidity and mortality of autologous hematopoietic transplants for children with malignant central nervous system tumors: the ‘Head Start’ trials, 1991–2009

Abstract: Since 1991, three sequential prospective clinical trials have been conducted by the 'Head Start' (HS) Consortium in which young children with newly-diagnosed malignant central nervous system (CNS) tumors were treated with induction chemotherapy followed by single-cycle marrow-ablative chemotherapy and autologous hematopoietic rescue as a means of improving disease cure rate and quality of survival through avoidance (o 6 years old at diagnosis) or reduction (6-10 years old) of brain irradiation. Bone Marrow (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Seventeen percent of our patients were diagnosed with SOS, which is well within the range of incidence (4%‐25%) reported in previous studies 12 . The incidence of non‐SOS toxicities, including sepsis, mucositis, etc., encountered in our patients compared favorably with previous large studies reporting autologous transplants in children with various malignancies 13,14 . The excellent outcome of autologous transplants at our center during the study period, with no transplant‐related mortality, reflects the global trend of improving transplant outcomes 13,14 …”
Section: Discussionsupporting
confidence: 78%
“…Seventeen percent of our patients were diagnosed with SOS, which is well within the range of incidence (4%‐25%) reported in previous studies 12 . The incidence of non‐SOS toxicities, including sepsis, mucositis, etc., encountered in our patients compared favorably with previous large studies reporting autologous transplants in children with various malignancies 13,14 . The excellent outcome of autologous transplants at our center during the study period, with no transplant‐related mortality, reflects the global trend of improving transplant outcomes 13,14 …”
Section: Discussionsupporting
confidence: 78%
“…We found that the proportion of deaths due to TRM did not change over time. In contrast, others have noted reduced TRM over time when intensive therapies are introduced, such as for acute myeloid leukaemia treatment and HSCT ( Jastaniah et al , 2012 ; Altshuler et al , 2016 ). One explanation for this discrepancy is the different metric used, as we evaluated the proportion of deaths as opposed to the proportion of patients with TRM.…”
Section: Discussionmentioning
confidence: 98%
“…High‐dose chemotherapy followed by autologous hematopoietic stem cell transplantation to allow for bone marrow reconstitution is a well‐recognised treatment option for children with solid tumours, lymphoma and brain tumours but carries considerable risks of infectious morbidity and mortality. In the past two decades, improvements in transplant approaches and supportive care have had major impact on the occurrence of infectious complications in this setting . This is particularly true for the advent of new and more versatile antifungal agents and the development of newer diagnostic tools to diagnose invasive fungal diseases (IFDs) that have led to an optimisation of treatment algorithms and better control of IFDs but also, increased utilisation of antifungal drugs and diagnostics …”
Section: Introductionmentioning
confidence: 99%